2016
DOI: 10.1021/acs.oprd.6b00131
|View full text |Cite
|
Sign up to set email alerts
|

Flow Grignard and Lithiation: Screening Tools and Development of Continuous Processes for a Benzyl Alcohol Starting Material

Abstract: Efficient continuous Grignard and lithiation processes were developed to produce one of the key regulatory starting materials for the production of edivoxetine hydrochoride. For the Grignard process, organometallic reagent formation, Bouveault formylation, reduction, and workup steps were run in continuous stirred tank reactors (CSTRs). The lithiation utilized a hybrid approach where plug flow reactors (PFRs) were used for the metal halogen exchange and Bouveault formylation steps, while the reduction and work… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 27 publications
1
35
0
Order By: Relevance
“…This corresponded to a throughput of 28.5 g h −1 . Two industrial research groups demonstrated the challenges for continuous‐flow lithiation scale‐up . Similar to our observations, the main issues involved guaranteeing isothermal conditions, even in microstructured reactors, the feedstock quality and exclusion of moisture, and operational problems, such as pressure build‐up in pumps, valves or precoolers and flow pulsations due to the formation of gaseous phases.…”
Section: Resultssupporting
confidence: 73%
See 2 more Smart Citations
“…This corresponded to a throughput of 28.5 g h −1 . Two industrial research groups demonstrated the challenges for continuous‐flow lithiation scale‐up . Similar to our observations, the main issues involved guaranteeing isothermal conditions, even in microstructured reactors, the feedstock quality and exclusion of moisture, and operational problems, such as pressure build‐up in pumps, valves or precoolers and flow pulsations due to the formation of gaseous phases.…”
Section: Resultssupporting
confidence: 73%
“…Many common pump types are incompatible with alkyllithium solutions. Despite the limited injection volume, in general syringe pumps or sample loops are preferred for safety and chemical resistance reasons . At the outlet of the reactor, the mixture was quenched at room temperature by using D 2 O.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For production purpose, Continuous Stirred Tank Reactors (CSTR) have been shown to better handle high exothermic reactions in which one or more of the reagents is a solid, as in the synthesis of Grignard reagents …”
Section: Magnesium Derivativesmentioning
confidence: 99%
“…[56] For production purpose, Continuous Stirred Tank Reactors (CSTR) have been shown to better handle high exothermic reactions in which one or more of the reagents is a solid, as in the synthesis of Grignard reagents. [57,58] Other processes are based on the use of thermostated columns containing some rotating blades where granulated magnesium (diam. 1-3 mm) was inserted from the top and the halide pumped from the bottom.…”
Section: Metal Insertionmentioning
confidence: 99%